YouTube as Learning Medium for Promoting EFL Students’ Reading Habit and Motivation - Adimawati Helingo (Journal of English Language and Education, 2022)
The massive English YouTube videos uploaded on YouTube provide potential for anyone to be able to study independently, including students. This study intends to investigate the use of YouTube media among EFL students in maintaining their motivation reading English text and their interest in learning English inside and outside classroom. This qualitative study used the interview to collect research data from 7 students as respondents. The selection of 7 students was based on the habit of these students accessing YouTube videos more often than most other students. The results showed that 5 students felt that watching YouTube with a certain intensity in a day could encourage the desire to study harder and be interested in learning English. Some who use YouTube as a learning tool can improve reading habits or interests and also improve other skills such as listening, speaking and other things. With many features, so that everyone can access anything they want to access in YouTube with their purposes, including improving reading habits and motivation